Better to stay or go? A longitudinal study of mobility over the educational life course - Sweet, Amy; Harris, Richard; Manley, David (International Journal of Population Data Science, 2018)
Background There has been substantial discussion in the literature about where you grow up and if whether or not you experience social and spatial mobility during childhood has substantial bearing upon later life achievement (Pribesh and Downey, 1999; Gasper et al, 2010; Sharkey and Elwert, 2011). Objectives This paper utilises data from the National Pupil Database (NPD) and a quantitative framework to explore the impact of residential mobility on educational outcomes. Many previous studies of neighbourhood mobility have used point in time measures when studying inequality, which means that an individual’s neighbourhood trajectory is overlooked. Data/Methods We follow a single cohort of pupils’ over an eleven year time period to analyse their mobility along with their individual characteristics to provide a clear understanding of who is moving and the impact this has on them in terms of educational attainment. We also use the index of multiple deprivation as a measure of neighbourhood wealth to determine to what extent children are able to ’trade up’ in terms of neighbourhood. Findings Our findings show that moving home has a negative impact on educational attainment compared to those that stay in the same location throughout the educational life cycle. Those that ‘trade up’ in terms of quality of neighbourhood still do not achieve the same educational outcomes as their peers who live in a lower deprived neighbourhood throughout their schooling. Conclusion Residential mobility between deprived areas, as shown in this paper, has more of an impact than just being ‘stuck in place’. It is not purely a case of where you live determining your outcomes, but also how often you move home in childhood and adolescence.